2021
DOI: 10.1002/arch.21839
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quercetin combined with nucleopolyhedrovirus on the growth and immune response in the silkworm (Bombyx mori)

Abstract: Flavonoids are secondary metabolites that help plants resist insect attack. It can resist insect attack by inhibiting insect immune defense, and pathogens can also inhibit insect immune defense. It is speculated that the combination of flavonoids and pathogens may inhibit the immune defense and have stronger toxicity to silkworm. In this study, the combined treatment of quercetin with Bombyx mori nuclear polyhedrosis virus (BmNPV) had significant negative effects on the growth and survival of silkworm compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Quercetin (C5H10O7; Figure 1), a flavonol widely present in nature in the form of glucosides (Ulusoy and Sanlier, 2020), is one of the main components of different TCM, including Radix Bupleuri, Mulberry leaves, Sophorae Fructus, Inulae Flos, and Crataegi Fructus (Ding et al, 2021a;Shi et al, 2021;Tu et al, 2022). Many studies have demonstrated that quercetin has a wide range of pharmacological effects such as anti-cancer, antibacterial, anti-oxidation, and memory impairment improvement (Horowitz and Zunszain, 2015;Suganthy et al, 2016;Babaei et al, 2018a;Kashyap et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (C5H10O7; Figure 1), a flavonol widely present in nature in the form of glucosides (Ulusoy and Sanlier, 2020), is one of the main components of different TCM, including Radix Bupleuri, Mulberry leaves, Sophorae Fructus, Inulae Flos, and Crataegi Fructus (Ding et al, 2021a;Shi et al, 2021;Tu et al, 2022). Many studies have demonstrated that quercetin has a wide range of pharmacological effects such as anti-cancer, antibacterial, anti-oxidation, and memory impairment improvement (Horowitz and Zunszain, 2015;Suganthy et al, 2016;Babaei et al, 2018a;Kashyap et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…and Callosobruchus chinensis (Lattanzio et al, 2000;Salunke et al, 2005;Selin-Rani et al, 2016;Cui et al, 2019). The synergistic effect of quercetin and nucleopolyhedrovirus was also found (Shi et al, 2021). However, quercetin metabolism by microbes is still unclear (Aboshi et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Quercetin is considered to be a kind of flavonoid widely present in terrestrial plants and herbal medicines which helps plants resist herbivore attack ( Simmonds, 2003 ; Selin-Rani et al, 2016 ; Shi et al, 2021 ), and induces expressions of some detoxification enzymes in insects ( Zhang et al, 2012 ; Shi et al, 2021 ). Quercetin is assumed to be an ecofriendly alternative compound not only for S. litura but also for Lymantria dispar , Helicoverpa zea , Oedaleus asiaticus , Aphis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin, a naphthoquinone isolated from Lithospermum erythrorhizon , is well-known for its strong anti-tumor effects ( Sun et al, 2022 ). It has been used to treat various cancers, such as colon, renal, and lung cancer ( Pan et al, 2021 ; Shi G. et al, 2021 ; Tsai et al, 2021 ). To elucidate the roles and mechanisms of Shikonin on breast cancer, Wei et al performed a study on MCF-7 cells with Shikonin treatment ( Wei et al, 2016 ).…”
Section: Exosomes Modulators From Compounds Isolated From Tcmmentioning
confidence: 99%
“…Shikonin, a naphthoquinone isolated from Lithospermum erythrorhizon, is well-known for its strong anti-tumor effects (Sun et al, 2022). It has been used to treat various cancers, such as colon, renal, and lung cancer (Pan et al, 2021;Shi G. et al, 2021;Tsai et al, 2021) Frontiers in Pharmacology frontiersin.org 7 cells with Shikonin treatment (Wei et al, 2016). Shikonin inhibited MCF-7 cell proliferation and exosome secretion from MCF-7 cells with a positive relationship.…”
Section: Shikoninmentioning
confidence: 99%